Impact of an Outpatient Pharmacist Intervention on Medication Discrepancies and Health Care Resource Utilization in Posthospitalization Care Transitions - Emily M. Hawes; Whitney D. Maxwell; Sarah F. White; Jesica Mangun; Feng-Chang Lin (SAGE Publishing, 2014)
Purpose: Medication errors related to hospital discharge result in rehospitalization and emergency department (ED) visits, yet no systematic approach has been implemented nationally to decrease these medication errors. Pharmacist involvement during postdischarge transitions of care may be an important strategy to prevent and correct medication discrepancies and reduce costly rehospitalization and ED visits. Methods: This prospective, randomized, open-label, pilot study evaluated the effect of a pharmacy clinic visit focused on medication reconciliation and patient education after hospital discharge on the incidence of rehospitalization and ED visits and the resolution of medication discrepancies. Results: Of the 61 subjects included in the study, 33 (54%) had medication discrepancies identified at discharge. Fifty percent of medication discrepancies were resolved in subjects randomized to the pharmacist intervention arm compared with 9.5% in the usual care arm ( P = .015). Patients randomized to the intervention arm had significantly lower rates of the primary composite outcome of 30-day rehospitalization and ED visits compared with the usual care arm (0% vs 40.5%, P < .001). Conclusion: A pharmacist-driven intervention focused on patient education and medication reconciliation after discharge improved medication use and reduced health care resource utilization in this pilot study.